PELAKSANAAN PEMBELAJARAN DI MASA PANDEMI COVID-19 DARI SUDUT PANDANG MAHASISWA DI UNIVERSITAS ISLAM KUANTAN SINGINGI - Dwi Putri Musdansi; Rosa Murwindra; Nofri Yuhelman; Windri Anita (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
This study aims to analyze the implementation of learning in the Covid-19 era from the preception of student's. This research with a quantitative approach uses a number of samples from Isaac and Micheal. The study population was all UNIKS students in the odd and even semesters of the 2020/2021 academic year. The samples taken were 341 respondents using a significance level of 1%. The sampling technique used is simple random sampling with sampling using SPSS, namely simple sampling. The sample in this study was 65.1% female and 34.9% male. The data collection technique used the